Assessment of biomass ash applications in soil and cement mortars. (May 2019) - Tosti, Lorenzo; van Zomeren, André; Pels, Jan R.; Dijkstra, Joris J.; Comans, Rob N.J.
Abstract: The pH-dependent availability and leaching of major and trace elements was investigated for a wide range of biomass ash from different fuels and conversion technologies. A technical and environmental assessment of selected biomass ash for application in soil or cement mortars was performed, using both the total content and leaching of elements. A large variation in biomass ash composition, yet consistent pH dependent leaching patterns were observed for most elements and conversion technologies. Chromium showed a distinct behaviour which was hypothesized to reflect redox conditions during conversion of the biomass. The leaching based approach was found to provide a more realistic assessment of the availability of desired (i.e. nutrients) and undesired elements (i.e. contaminants) in soil systems. When applied to a reference soil at a rate of 2% by weight, the selected biomass ash increased the concentration of particularly Cr, Mo and Zn in soil solution to a level of concern. For cement applications, the release of Ba, Cr and Mo can become of concern during the second life stage, but the release was not attributed to the included biomass ash. Both soil and cement matrixes were found to control the release of elements such as Cu, V and Ni (soil) and As, Cr and Mo (cement) when compared to the released from pure biomass ash, underlining the importance of evaluating the availability and leaching of desired and undesired elements in the application scenario. Given current regulatory criteria, beneficial utilization of biomass ash in cement may be more feasible than in soil, but regulatory criteria based on leaching rather than total content of elements may widen the application potential of biomass ash. Highlights: Assessing biomass ash use according to total and leaching based approaches. Consistent leaching pattern of elements despite variation in biomass ash content. Leaching approach provides a more realistic assessment of elements' availability. Soil and cement matrices control elements' release compared to biomass ash release. Current regulations would favour utilization of biomass ash in cement and not soil.